DEVELOPING SPEAKING MATERIAL FOR TEACHING SPEAKING BASED ON COMMUNICATIVE LANGUAGE TEACHING FOR SECOND SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM MUHAMMADIYAH UNIVERSITY OF METRO - Fitri Palupi Kusumawati; Ratna Puspita Sari (Intensive Journal, 2019)
This Research and Development (R&D) aimed to develop as a learning media using the assessment from the experts and determine the students' response to the Speaking Textbook in improving speaking ability. It was conducted using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation. The result obtained from the small group, field test and 5 phase of the ADDIE model. Assessing the reliability of the speaking module showed the following: 1) The Content expert gave percentage 83% which means developed the content gets "Good" category. 2) The Design expert gave percentage 71,4% which means developed the design gets “Good” category. 3) The language expert gave percentage 80% which means developed the language gets “Good” category.4) The field test questionnaires students responses in the second semester of English Department gave percentage 83,235% which means the speaking module gets "Very Positive" category. 5) The small group showed the responses from students were good responses. Based on the result, it presents that the speaking materials based on communicative language teaching (CLT) module can be learned attractively and interestingly.